The Short Fiction of Pablo Palacio: A Literary Response to the Existential-Linguistic Phenomenon - Silva Samaniego, Christian Eduardo (2026)
The present work aims to unravel the animal-linguistic meaning found in the short stories of Ecuadorian writer Pablo Palacio, based on Heideggerian metaphysics and Derridian deconstruction. To achieve this, it is necessary to recognize the variety of aspects proposed by his narrative, where a multiplicity of eccentric characters, situated on the boundary between human and non-human existence, converge. In order to analyze this work, it is essential to perceive Palacio’s short stories as synods of a brief dialectical approach to the linguistic framework of existence. To this end, the meanings and forms of the characters, events, and temporalities are examined, always tied to a space that is not only historical but also ontological.